A crystallization-controlled perovskite solar cell and a method for preparing the same
By using prolymide and proline in perovskite solar cells to regulate the crystallization process, the problems of poor stability and photoelectric performance of perovskite solar cells are solved, and higher photoelectric conversion efficiency and stability are achieved.
Patent Information
- Application Number
- CN202211088440.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-07
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Perovskite solar cells have poor stability, mainly due to the microscopic defects of their materials that cause carrier transport to be blocked, affecting photoelectric performance.
By using prolymide as a dopant and proline as a modifier during the preparation of perovskite solar cells, the crystallization process of perovskite materials is regulated, the defect density is reduced, the lattice structure is optimized, and the carrier loss is reduced.
The photoelectric performance and stability of perovskite solar cells are improved, the crystallinity and surface flatness of the perovskite layer are enhanced, the carrier binding and leakage current are reduced, and the photoelectric conversion efficiency is improved.
Smart Images

Figure CN115332455B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photovoltaic materials and devices, and in particular relates to a crystallization-controlled perovskite solar cell and a preparation method thereof. Background Art
[0002] In recent years, energy issues have received widespread attention. Perovskite solar cells, as a new type of solar cell, have been widely studied for their excellent photovoltaic performance and low manufacturing cost. However, existing studies have shown that the poor stability of perovskite solar cells has always been a serious problem hindering their industrialization. One of the key reasons affecting their optoelectronic performance and stability is the microscopic defects of their perovskite materials.
[0003] The common structure of perovskite solar cells includes a conductive substrate, an electron conduction layer, a perovskite light-absorbing layer, a hole conduction layer, and a metal electrode. Existing studies have shown that organic-inorganic hybrid perovskite materials, as a semiconductor material, generate free carriers through the photoelectric effect under light conditions. After connecting to an external circuit, the free electrons and free holes move toward each other inside the device through the energy level matching effect of each stacked material, thereby generating voltage and current. This is the working principle of perovskite solar cells.
[0004] Perovskite photovoltaic materials have microscopic defects such as grain boundaries, ion defects, and dangling bonds. These defects will introduce deep defect energy levels, thereby restricting the normal transport of free carriers, and will also cause adverse phenomena such as non-radiative recombination, which will lead to a decrease in the overall performance of solar cells. The passivation method using Lewis acid-base reaction (for example, using certain small molecule organic substances) is a commonly used defect passivation method. Additives react with the precursor in the perovskite precursor, thereby increasing the reaction energy barrier and slowing down the crystallization rate during the perovskite crystallization process, which can improve the crystallinity, thereby reducing the generation of defects and neutralizing the adverse effects caused by ion defects. Summary of the invention
[0005] The object of the present invention is to provide a perovskite solar cell with regulated crystallization and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a perovskite solar cell after crystallization control, the method comprising:
[0008] (1) Blowing the cleaned conductive substrate dry with nitrogen and performing UV-ozone treatment;
[0009] (2) preparing an electronic conduction layer on the conductive base layer;
[0010] (3) preparing a prolineamide calcium-doped perovskite light-absorbing layer on the electron conduction layer;
[0011] (4) Preparing a proline modified layer on the perovskite light absorbing layer;
[0012] (5) preparing a hole conduction layer on the proline modified layer;
[0013] (6) Sputtering a metal electrode on the hole conduction layer using a magnetron sputtering apparatus or an evaporation deposition method to prepare a metal electrode layer.
[0014] As a further improvement of the present invention, step (1) comprises:
[0015] After the conductive substrate is partitioned by laser engraving, the conductive substrate is scrubbed with a non-woven fabric soaked in a substrate cleaning solution, and then rinsed with deionized water and anhydrous ethanol in sequence. After the rinsing is completed, ultrasonic cleaning is performed with the substrate cleaning solution, ethanol, deionized water, acetone, and ethanol in sequence for 15 minutes to obtain a clean conductive base layer;
[0016] The substrate cleaning solution is obtained by uniformly mixing deionized water, glass cleaner and dishwashing liquid in a volume ratio of 30:5:1.
[0017] As a further improvement of the present invention, the step (2) comprises:
[0018] In an air environment and at room temperature, 70 μL of the electron conduction layer solution is taken with a pipette and spin-coated onto the conductive substrate at a spin-coating speed of 3000 rpm. After the spin-coating is completed, the solution is annealed on a 150° C. hot stage for 30 minutes, and then subjected to UV-ozone treatment to prepare an electron conduction layer.
[0019] The electronic conduction layer solution is obtained by uniformly mixing a tin dioxide nanocrystal solution and deionized water in a ratio of 1:4, and filtering the mixture through a syringe and a filter nozzle combination.
[0020] As a further improvement of the present invention, the step (3) comprises:
[0021] In a nitrogen glove box, 80-100 μL of a lead iodide precursor solution is spin-coated onto the electron conduction layer at a speed of 1500 rpm and an acceleration of 800 m / s². After the spin coating, the lead iodide layer is annealed on a hot plate at 70°C for 1 minute to form a lead iodide layer.
[0022] After nitrogen is blown on the surface, 100-110 μL of ammonium salt precursor solution is spin-coated on the lead iodide layer at a speed of 1500-1700 rpm; heated at 70° C. for 50-60 seconds in a nitrogen glove box, and then heated to 150° C. in an indoor air environment with a humidity of 45%-60%, and kept warm for 15 minutes to obtain a prolineamide-doped perovskite light-absorbing layer.
[0023] As a further improvement of the present invention, the lead iodide precursor solution is prepared by mixing lead iodide and prolineamide in a certain proportion, adding the mixture to a solvent of N,N-dimethylformamide and dimethyl sulfoxide mixed in a ratio of 9:1 to dissolve the mixture so that the concentration of prolineamide is 0.5-1.5 mg / ml, continuously heating and stirring the mixture at 60-70° C., and filtering the mixture through a syringe and a filter tip combination.
[0024] As a further improvement of the present invention, the ammonium salt precursor solution is obtained by adding iodoformamidine, chloromethylamine and bromomethylamine in a mass ratio of (9-10):(2-1):1 to an isopropanol solution and dissolving the solution, and then filtering the solution through a syringe and a filter tip combination.
[0025] As a further improvement of the present invention, step (4) comprises:
[0026] Proline is added to a mixed solvent of ultrapure water, N,N-dimethylformamide, and dimethyl sulfoxide in a volume ratio of 2:7:1, so that the concentration of proline is 0.3-1.2 mg / ml;
[0027] In a nitrogen glove box, 40 μL of the proline modification layer solution was spin-coated onto the perovskite layer at a rotation speed of 4000 rpm for 30 seconds, and then heated and annealed at 75° C. for 1 minute to prepare a proline modification layer.
[0028] As a further improvement of the present invention, step (5) comprises: spin coating 50 μL of the hole conduction layer solution on the proline modified layer at a speed of 4000 rpm for 30 seconds in a nitrogen glove box to prepare a hole conduction layer, and after the spin coating, placing the layer in a drying oven for oxidation for 24 hours.
[0029] As a further improvement of the present invention, the hole conducting layer solution is prepared as follows:
[0030] Using acetonitrile as solvent to dissolve Li-TFSI to prepare a Li-TFSI acetonitrile solution with a concentration of 520 mg / ml;
[0031] Spiro-OMeTAD is dissolved in chlorobenzene as a solvent, tBP and the Li-TFSI acetonitrile solution are added, and then filtered through a syringe and filter tip combination to obtain the product.
[0032] On the other hand, a perovskite solar cell prepared as in the first aspect is provided.
[0033] The beneficial effects of adopting the above technical solution are:
[0034] The present invention provides a method for preparing a perovskite solar cell. Prolineamide, as a small molecule organic substance, plays a role of condensation nuclei during perovskite crystallization, so as to improve the film-forming property of the perovskite material, increase the perovskite crystal grain size, and reduce the loss of carriers. The amino group and carbonyl group possessed by the prolineamide can form coordination bonds and hydrogen bonds with various defects in the perovskite, thereby optimizing the lattice structure distorted by the defects. The Lewis basic functional group (such as the amino group) can form coordination bonds and hydrogen bonds with the PbI type antisite defects (lead ions replace iodine ions) and uncoordinated Pb 2+ The defects are coordinated to offset their binding ability on free carriers, and there are many dangling bonds formed by incompletely coordinated ions on the surface of the perovskite layer. As an interface defect, the dangling bonds have a strong inhibitory effect on the transport of carriers. The adverse effect of dangling bonds on carrier transport can be weakened by the coordination passivation of proline small molecules in the proline modified layer. The photoelectric performance of the cell device is improved relative to the untreated perovskite solar cell device. After connecting to the external circuit, the lattice structure allows the perovskite solar cell to receive continuous light and absorb excitons. The photogenerated carriers flow into the external circuit under the action of the internal potential difference formed by the structure, forming a stable photogenerated current.
[0035] The perovskite solar cell prepared by the method provided by the present invention has a perovskite light-absorbing layer film that shows stronger crystallinity and a smoother surface after being doped with prolineamide, and the dangling bonds on the surface of the perovskite layer between the interface of the perovskite light-absorbing layer and the hole conduction layer can be passivated by proline, thereby reducing the binding of deep energy level defects on carriers, and can also effectively reduce the contact between the electron conduction layer and the hole conduction layer, reduce leakage current, improve photoelectric conversion efficiency, and help block the infiltration of oxygen and reduce the oxidation of the perovskite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 Schematic diagram of the structure of a perovskite solar cell after crystallization control according to Example 1 of the present invention.
[0038] Figure 2 The current density-voltage (JV) curve test diagram of the perovskite solar cells of Examples 1, 2, 3 and Comparative Examples 1 and 2.
[0039] Figure 3The current density-voltage (JV) curve test diagram of the perovskite solar cells of Examples 1, 4, 5 and Comparative Examples 1 and 3.
[0040] Figure 4 This is a quantum efficiency test diagram of the perovskite solar cell in Example 1 and Comparative Example 1.
[0041] Figure 5 1 is an electrochemical impedance spectroscopy (EIS) test graph of the perovskite solar cell in Example 1 and Comparative Example 1 according to the present invention.
[0042] Figure 6 It is a test graph of the dark current density-voltage (Dark JV) curve of the perovskite solar cell in Example 1 and Comparative Example 1 according to the present invention.
[0043] Figure 7 This is a space charge limited current method (SCLC) test diagram of the perovskite layer material in the perovskite solar cell in Comparative Example 1 of the present invention.
[0044] Figure 8 This is a space charge limited current method (SCLC) test diagram of the perovskite layer material in the perovskite solar cell according to Example 1 of the present invention.
[0045] Fig. 9 1 is an X-ray diffraction (XRD) spectrum of the perovskite layer material of the perovskite solar cell according to Example 1 and Comparative Example 1 of the present invention.
[0046] Fig.10 1 is the UV-visible absorption spectrum of the perovskite layer material of the perovskite solar cell according to Example 1 and Comparative Example 1 of the present invention.
[0047] Fig.11 1 is the ultraviolet photoelectron spectrum of the perovskite layer material of the perovskite solar cell according to Example 1 and Comparative Example 1 of the present invention.
[0048] Fig.12 This is a test graph of the photoelectric conversion efficiency stability of the perovskite solar cells in Example 1 and Comparative Example 1 according to the present invention stored in a nitrogen glove box environment away from light for 720 hours.
[0049] Fig.13 This is a test graph of the stability of the photoelectric conversion efficiency of the perovskite solar cells in Example 1 and Comparative Example 1 according to the present invention under continuous irradiation with a standard solar intensity for 240 hours.
[0050] Fig.14 This is a test graph of the photoelectric conversion efficiency stability of the perovskite solar cells in Example 1 and Comparative Example 1 according to the present invention when stored in an air environment with a humidity of 40%-60% for 720 hours. DETAILED DESCRIPTION
[0051] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention is clearly and completely described below in conjunction with specific embodiments.
[0052] Embodiment 1:
[0053] An embodiment of a method for preparing a perovskite solar cell with controlled crystallization comprises the following steps:
[0054] 1. Conductive base treatment
[0055] 1-1) Preparing a substrate cleaning solution: mixing deionized water, glass cleaner, and dishwashing liquid in a volume ratio of 30:5:1 to obtain a substrate cleaning solution;
[0056] 1-2) ITO conductive glass is used, with a square resistance of 15, a transmittance of 93%, and a substrate size of 15*15mm 2 , 0.7 mm thick;
[0057] 1-3) After the conductive substrate is partitioned by laser engraving, the conductive substrate is scrubbed with a non-woven fabric soaked in a substrate cleaning solution, and then rinsed with deionized water and anhydrous ethanol in sequence. After the rinsing is completed, ultrasonic cleaning is performed with a substrate cleaning solution, ethanol, deionized water, acetone, and ethanol in sequence to obtain a clean conductive base layer;
[0058] 1-4) The cleaned conductive substrate is blown dry with nitrogen and subjected to UV-ozone treatment for 15 minutes.
[0059] 2. Prepare an electronic conduction layer on a conductive base layer
[0060] 2-1) Preparation of electron conduction layer solution: Use a pipette to take 500 μL of tin dioxide nanocrystal solution and 2 ml of deionized water, mix them evenly, and filter them through a syringe and filter tip combination to obtain an electron conduction layer solution;
[0061] 2-2) In an air environment and at room temperature, 70 μL of the electron conduction layer solution is taken with a pipette and spin-coated onto the conductive substrate at a spin-coating speed of 3000 rpm. After the spin-coating is completed, the solution is annealed on a 150° C. hot plate for 30 minutes, and then subjected to UV-ozone treatment to prepare an electron conduction layer.
[0062] 3. Preparation of prolineamide-doped perovskite light-absorbing layer on the electron conduction layer
[0063] 3-1) Preparing a lead iodide precursor solution: dissolving 600 mg of lead iodide and 1 mg of proline amide in a mixed solvent of 900 μL of DMF and 100 μL of DMSO to obtain a proline amide concentration of 1 mg / ml, heating and stirring the mixture at 70° C. for 12 hours using a magnetic stirrer, and then filtering the mixture using a syringe and a filter tip combination to prepare a lead iodide precursor solution;
[0064] 3-2) Preparation of ammonium salt precursor solution: using 1 ml of isopropanol as solvent, dissolving 60 mg of FAI, 6 mg of MACl, and 6 mg of MABr in a certain proportion, and then filtering with a syringe and a filter tip combination to prepare an ammonium salt precursor solution;
[0065] 3-3) Preparation of lead iodide layer: In a nitrogen glove box, 80-100 μL of lead iodide precursor solution is spin-coated onto the electron conduction layer at a speed of 1500 rpm and an acceleration of 800 m / s². After the spin coating, annealing is performed on a hot plate at 70°C for 1 minute to form a lead iodide layer;
[0066] 3-4) Preparation of perovskite light-absorbing layer: After blowing nitrogen on the surface, 100 μL of ammonium salt precursor solution is spin-coated on the lead iodide layer at a speed of 1500-1700 rpm, and then heated at 70°C in a nitrogen glove box for 50-60 seconds, and then heated to 150°C in an indoor air environment with a humidity of 45%-60%, and kept warm for 15 minutes to obtain a prolineamide-doped perovskite light-absorbing layer.
[0067] 4. Preparation of proline modified layer on perovskite light absorbing layer
[0068] 4-1) Preparation of Proline Modified Layer Solution
[0069] Prepare 1 mL of mixed solvent with ultrapure water: DMF: DMSO = 200 μL: 700 μL: 100 μL, add 0.75 mg of proline to make the proline concentration 0.75 mg / ml, heat to 70°C and stir until dissolved;
[0070] 4-2) In a nitrogen glove box, 40 μL of the proline modification layer solution was spin-coated onto the perovskite layer at a rotation speed of 4000 rpm for 30 seconds, and then heated and annealed at 75° C. for 1 minute to prepare a proline modification layer.
[0071] 5. Preparation of hole conduction layer on proline modified layer
[0072] 5-1) Preparation of hole conduction layer solution: dissolve Li-TFSI in acetonitrile to prepare a Li-TFSI acetonitrile solution with a concentration of 520 mg / ml; dissolve 0.0723 g of Spiro-MeOTAD in 1 ml of chlorobenzene as solvent, add 28.5 μL of tBP and 17.5 μL of Li-TFSI acetonitrile solution, stir for 1 hour, and filter with a syringe and filter tip combination to obtain a hole conduction layer solution;
[0073] 5-2) In a nitrogen glove box, 50 μL of the hole conduction layer solution was spin coated onto the proline modified layer at 4000 rpm for 30 seconds to prepare a hole conduction layer. After the spin coating, the layer was placed in a culture dish, and the culture dish was placed in a drying oven for oxidation under air conditions for 24 hours.
[0074] 6. Preparation of metal electrode layer
[0075] The metal electrode layer is prepared by sputtering a metal silver (Ag) electrode on the hole conduction layer using an evaporation deposition method.
[0076] Embodiment 2:
[0077] 1. Conductive base treatment
[0078] 1-1) Preparing a substrate cleaning solution: mixing deionized water, glass cleaner, and dishwashing liquid in a volume ratio of 30:5:1 to obtain a substrate cleaning solution;
[0079] 1-2) ITO conductive glass is used, with a square resistance of 15, a transmittance of 93%, and a substrate size of 15*15mm 2 , 0.7 mm thick;
[0080] 1-3) After the conductive substrate is partitioned by laser engraving, the conductive substrate is scrubbed with a non-woven fabric soaked in a substrate cleaning solution, and then rinsed with deionized water and anhydrous ethanol in sequence. After the rinsing is completed, ultrasonic cleaning is performed with a substrate cleaning solution, ethanol, deionized water, acetone, and ethanol in sequence to obtain a clean conductive base layer;
[0081] 1-4) The cleaned conductive substrate is blown dry with nitrogen and subjected to UV-ozone treatment for 15 minutes.
[0082] 2. Prepare an electronic conduction layer on a conductive base layer
[0083] 2-1) Preparation of electron conduction layer solution: Use a pipette to take 500 μL of tin dioxide nanocrystal solution and 2 ml of deionized water, mix them evenly, and filter them through a syringe and filter tip combination to obtain an electron conduction layer solution;
[0084] 2-2) In an air environment and at room temperature, 70 μL of the electron conduction layer solution is taken with a pipette and spin-coated onto the conductive substrate at a spin-coating speed of 3000 rpm. After the spin-coating is completed, the solution is annealed on a 150° C. hot plate for 30 minutes, and then subjected to UV-ozone treatment to prepare an electron conduction layer.
[0085] 3. Preparation of prolineamide-doped perovskite light-absorbing layer on the electron conduction layer
[0086] 3-1) Preparing a lead iodide precursor solution: dissolving 600 mg of lead iodide and 0.5 mg of proline amide in a mixed solvent of 900 μL of DMF and 100 μL of DMSO to obtain a proline amide concentration of 0.5 mg / ml, heating and stirring at 70° C. for 12 hours with magnetic stirring, and then filtering with a syringe and filter tip combination to prepare a lead iodide precursor solution;
[0087] 3-2) Preparation of ammonium salt precursor solution: using 1 ml of isopropanol as solvent, dissolving 60 mg of FAI, 6 mg of MACl, and 6 mg of MABr in a certain proportion, and then filtering with a syringe and a filter tip combination to prepare an ammonium salt precursor solution;
[0088] 3-3) Preparation of lead iodide layer: In a nitrogen glove box, 80-100 μL of lead iodide precursor solution is spin-coated onto the electron conduction layer at a speed of 1500 rpm and an acceleration of 800 m / s². After the spin coating, annealing is performed on a hot plate at 70°C for 1 minute to form a lead iodide layer;
[0089] 3-4) Preparation of perovskite light-absorbing layer: After blowing nitrogen on the surface, 100 μL of ammonium salt precursor solution is spin-coated on the lead iodide layer at a speed of 1500-1700 rpm, and then heated at 70°C in a nitrogen glove box for 50-60 seconds, and then heated to 150°C in an indoor air environment with a humidity of 45%-60%, and kept warm for 15 minutes to obtain a prolineamide-doped perovskite light-absorbing layer.
[0090] 4. Preparation of proline modified layer on perovskite light absorbing layer
[0091] 4-1) Preparation of Proline Modified Layer Solution
[0092] Prepare 1 mL of mixed solvent with ultrapure water: DMF: DMSO = 200 μL: 700 μL: 100 μL, add 0.75 mg of proline, heat to 70°C and stir until dissolved;
[0093] 4-2) In a nitrogen glove box, 40 μL of the proline modification layer solution was spin-coated onto the perovskite layer at a rotation speed of 4000 rpm for 30 seconds, and then heated and annealed at 75° C. for 1 minute to prepare a proline modification layer.
[0094] 5. Preparation of hole conduction layer on proline modified layer
[0095] 5-1) Preparation of hole conduction layer solution: dissolve Li-TFSI in acetonitrile to prepare a Li-TFSI acetonitrile solution with a concentration of 520 mg / ml; dissolve 0.0723 g of Spiro-MeOTAD in 1 ml of chlorobenzene as solvent, add 28.5 μL of tBP and 17.5 μL of Li-TFSI acetonitrile solution, stir for 1 hour, and filter with a syringe and filter tip combination to obtain a hole conduction layer solution;
[0096] 5-2) In a nitrogen glove box, 50 μL of the hole conduction layer solution was spin coated onto the proline modified layer at 4000 rpm for 30 seconds to prepare a hole conduction layer. After the spin coating, the layer was placed in a culture dish, and the culture dish was placed in a drying oven for oxidation under air conditions for 24 hours.
[0097] 6. Preparation of metal electrode layer
[0098] The metal electrode layer is prepared by sputtering a metal silver (Ag) electrode on the hole conduction layer using an evaporation deposition method.
[0099] Embodiment 3:
[0100] 1. Conductive base treatment
[0101] 1-1) Preparing a substrate cleaning solution: mixing deionized water, glass cleaner, and dishwashing liquid in a volume ratio of 30:5:1 to obtain a substrate cleaning solution;
[0102] 1-2) ITO conductive glass is used, with a square resistance of 15, a transmittance of 93%, and a substrate size of 15*15mm 2 , 0.7 mm thick;
[0103] 1-3) After the conductive substrate is partitioned by laser engraving, the conductive substrate is scrubbed with a non-woven fabric soaked in a substrate cleaning solution, and then rinsed with deionized water and anhydrous ethanol in sequence. After the rinsing is completed, ultrasonic cleaning is performed with a substrate cleaning solution, ethanol, deionized water, acetone, and ethanol in sequence to obtain a clean conductive base layer;
[0104] 1-4) The cleaned conductive substrate is blown dry with nitrogen and subjected to UV-ozone treatment for 15 minutes.
[0105] 2. Prepare an electronic conduction layer on a conductive base layer
[0106] 2-1) Preparation of electron conduction layer solution: Use a pipette to take 500 μL of tin dioxide nanocrystal solution and 2 ml of deionized water, mix them evenly, and filter them through a syringe and filter tip combination to obtain an electron conduction layer solution;
[0107] 2-2) In an air environment and at room temperature, 70 μL of the electron conduction layer solution is taken with a pipette and spin-coated onto the conductive substrate at a spin-coating speed of 3000 rpm. After the spin-coating is completed, the solution is annealed on a 150° C. hot plate for 30 minutes, and then subjected to UV-ozone treatment to prepare an electron conduction layer.
[0108] 3. Preparation of prolineamide-doped perovskite light-absorbing layer on the electron conduction layer
[0109] 3-1) Preparing a lead iodide precursor solution: dissolving 600 mg of lead iodide and 1.5 mg of proline amide in a mixed solvent of 900 μL of DMF and 100 μL of DMSO to obtain a proline amide concentration of 1.5 mg / ml, heating and stirring at 70° C. for 12 hours with magnetic stirring, and then filtering with a syringe and filter tip combination to prepare a lead iodide precursor solution;
[0110] 3-2) Preparation of ammonium salt precursor solution: using 1 ml of isopropanol as solvent, dissolving 60 mg of FAI, 6 mg of MACl, and 6 mg of MABr in a certain proportion, and then filtering with a syringe and a filter tip combination to prepare an ammonium salt precursor solution;
[0111] 3-3) Preparation of lead iodide layer: In a nitrogen glove box, 80-100 μL of lead iodide precursor solution is spin-coated onto the electron conduction layer at a speed of 1500 rpm and an acceleration of 800 m / s². After the spin coating, annealing is performed on a hot plate at 70°C for 1 minute to form a lead iodide layer;
[0112] 3-4) Preparation of perovskite light-absorbing layer: After blowing nitrogen on the surface, 100 μL of ammonium salt precursor solution is spin-coated on the lead iodide layer at a speed of 1500-1700 rpm, and then heated at 70°C in a nitrogen glove box for 50-60 seconds, and then heated to 150°C in an indoor air environment with a humidity of 45%-60%, and kept warm for 15 minutes to obtain a prolineamide-doped perovskite light-absorbing layer.
[0113] 4. Preparation of proline modified layer on perovskite light absorbing layer
[0114] 4-1) Preparation of Proline Modified Layer Solution
[0115] Prepare 1 mL of mixed solvent with ultrapure water: DMF: DMSO = 200 μL: 700 μL: 100 μL, add 0.75 mg of proline to make the proline concentration 0.75 mg / ml, heat to 70°C and stir until dissolved;
[0116] 4-2) In a nitrogen glove box, 40 μL of the proline modification layer solution was spin-coated onto the perovskite layer at a rotation speed of 4000 rpm for 30 seconds, and then heated and annealed at 75° C. for 1 minute to prepare a proline modification layer.
[0117] 5. Preparation of hole conduction layer on proline modified layer
[0118] 5-1) Preparation of hole conduction layer solution: dissolve Li-TFSI in acetonitrile to prepare a Li-TFSI acetonitrile solution with a concentration of 520 mg / ml; dissolve 0.0723 g of Spiro-MeOTAD in 1 ml of chlorobenzene as solvent, add 28.5 μL of tBP and 17.5 μL of Li-TFSI acetonitrile solution, stir for 1 hour, and filter with a syringe and filter tip combination to obtain a hole conduction layer solution;
[0119] 5-2) In a nitrogen glove box, 50 μL of the hole conduction layer solution was spin coated onto the proline modified layer at 4000 rpm for 30 seconds to prepare a hole conduction layer. After the spin coating, the layer was placed in a culture dish, and the culture dish was placed in a drying oven for oxidation under air conditions for 24 hours.
[0120] 6. Preparation of metal electrode layer
[0121] The metal electrode layer is prepared by sputtering a metal silver (Ag) electrode on the hole conduction layer using an evaporation deposition method.
[0122] Embodiment 4:
[0123] 1. Conductive base treatment
[0124] 1-1) Preparing a substrate cleaning solution: mixing deionized water, glass cleaner, and dishwashing liquid in a volume ratio of 30:5:1 to obtain a substrate cleaning solution;
[0125] 1-2) ITO conductive glass is used, with a square resistance of 15, a transmittance of 93%, and a substrate size of 15*15mm 2 , 0.7 mm thick;
[0126] 1-3) After the conductive substrate is partitioned by laser engraving, the conductive substrate is scrubbed with a non-woven fabric soaked in a substrate cleaning solution, and then rinsed with deionized water and anhydrous ethanol in sequence. After the rinsing is completed, ultrasonic cleaning is performed with a substrate cleaning solution, ethanol, deionized water, acetone, and ethanol in sequence to obtain a clean conductive base layer;
[0127] 1-4) The cleaned conductive substrate is blown dry with nitrogen and subjected to UV-ozone treatment for 15 minutes.
[0128] 2. Prepare an electronic conduction layer on a conductive base layer
[0129] 2-1) Preparation of electron conduction layer solution: Use a pipette to take 500 μL of tin dioxide nanocrystal solution and 2 ml of deionized water, mix them evenly, and filter them through a syringe and filter tip combination to obtain an electron conduction layer solution;
[0130] 2-2) In an air environment and at room temperature, 70 μL of the electron conduction layer solution is taken with a pipette and spin-coated onto the conductive substrate at a spin-coating speed of 3000 rpm. After the spin-coating is completed, the solution is annealed on a 150° C. hot plate for 30 minutes, and then subjected to UV-ozone treatment to prepare an electron conduction layer.
[0131] 3. Preparation of prolineamide-doped perovskite light-absorbing layer on the electron conduction layer
[0132] 3-1) Preparing a lead iodide precursor solution: dissolving 600 mg of lead iodide and 1 mg of proline amide in a mixed solvent of 900 μL of DMF and 100 μL of DMSO to obtain a proline amide concentration of 1 mg / ml, heating and stirring the mixture at 70° C. for 12 hours using a magnetic stirrer, and then filtering the mixture using a syringe and a filter tip combination to prepare a lead iodide precursor solution;
[0133] 3-2) Preparation of ammonium salt precursor solution: using 1 ml of isopropanol as solvent, dissolving 60 mg of FAI, 6 mg of MACl, and 6 mg of MABr in a certain proportion, and then filtering with a syringe and a filter tip combination to prepare an ammonium salt precursor solution;
[0134] 3-3) Preparation of lead iodide layer: In a nitrogen glove box, 80-100 μL of lead iodide precursor solution is spin-coated onto the electron conduction layer at a speed of 1500 rpm and an acceleration of 800 m / s². After the spin coating, annealing is performed on a hot plate at 70°C for 1 minute to form a lead iodide layer;
[0135] 3-4) Preparation of perovskite light-absorbing layer: After blowing nitrogen on the surface, 100 μL of ammonium salt precursor solution is spin-coated on the lead iodide layer at a speed of 1500-1700 rpm, and then heated at 70°C in a nitrogen glove box for 50-60 seconds, and then heated to 150°C in an indoor air environment with a humidity of 45%-60%, and kept warm for 15 minutes to obtain a prolineamide-doped perovskite light-absorbing layer.
[0136] 4. Preparation of proline modified layer on perovskite light absorbing layer
[0137] 4-1) Preparation of proline modification layer solution
[0138] Prepare 1 mL of mixed solvent with ultrapure water: DMF: DMSO = 200 μL: 700 μL: 100 μL, add 0.3 mg of proline to make the proline concentration 0.3 mg / ml, heat to 70°C and stir until dissolved;
[0139] 4-2) In a nitrogen glove box, 40 μL of the proline modification layer solution was spin-coated onto the perovskite layer at a rotation speed of 4000 rpm for 30 seconds, and then heated and annealed at 75° C. for 1 minute to prepare a proline modification layer.
[0140] 5. Preparation of hole conduction layer on proline modified layer
[0141] 5-1) Preparation of hole conduction layer solution: dissolve Li-TFSI in acetonitrile to prepare a Li-TFSI acetonitrile solution with a concentration of 520 mg / ml; dissolve 0.0723 g of Spiro-MeOTAD in 1 ml of chlorobenzene as solvent, add 28.5 μL of tBP and 17.5 μL of Li-TFSI acetonitrile solution, stir for 1 hour, and filter with a syringe and filter tip combination to obtain a hole conduction layer solution;
[0142] 5-2) In a nitrogen glove box, 50 μL of the hole conduction layer solution was spin coated onto the proline modified layer at 4000 rpm for 30 seconds to prepare a hole conduction layer. After the spin coating, the layer was placed in a culture dish, and the culture dish was placed in a drying oven for oxidation under air conditions for 24 hours.
[0143] 6. Preparation of metal electrode layer
[0144] The metal electrode layer is prepared by sputtering a metal silver (Ag) electrode on the hole conduction layer using an evaporation deposition method.
[0145] Embodiment 5:
[0146] 1. Conductive base treatment
[0147] 1-1) Preparing a substrate cleaning solution: mixing deionized water, glass cleaner, and dishwashing liquid in a volume ratio of 30:5:1 to obtain a substrate cleaning solution;
[0148] 1-2) ITO conductive glass is used, with a square resistance of 15, a transmittance of 93%, and a substrate size of 15*15mm 2 , 0.7 mm thick;
[0149] 1-3) After the conductive substrate is partitioned by laser engraving, the conductive substrate is scrubbed with a non-woven fabric soaked in a substrate cleaning solution, and then rinsed with deionized water and anhydrous ethanol in sequence. After the rinsing is completed, ultrasonic cleaning is performed with a substrate cleaning solution, ethanol, deionized water, acetone, and ethanol in sequence to obtain a clean conductive base layer;
[0150] 1-4) The cleaned conductive substrate is blown dry with nitrogen and subjected to UV-ozone treatment for 15 minutes.
[0151] 2. Prepare an electronic conduction layer on a conductive base layer
[0152] 2-1) Preparation of electron conduction layer solution: Use a pipette to take 500 μL of tin dioxide nanocrystal solution and 2 ml of deionized water, mix them evenly, and filter them through a syringe and filter tip combination to obtain an electron conduction layer solution;
[0153] 2-2) In an air environment and at room temperature, 70 μL of the electron conduction layer solution is taken with a pipette and spin-coated onto the conductive substrate at a spin-coating speed of 3000 rpm. After the spin-coating is completed, the solution is annealed on a 150° C. hot plate for 30 minutes, and then subjected to UV-ozone treatment to prepare an electron conduction layer.
[0154] 3. Preparation of prolineamide-doped perovskite light-absorbing layer on the electron conduction layer
[0155] 3-1) Preparing a lead iodide precursor solution: dissolving 600 mg of lead iodide and 1 mg of proline amide in a mixed solvent of 900 μL of DMF and 100 μL of DMSO to obtain a proline amide concentration of 1 mg / ml, heating and stirring the mixture at 70° C. for 12 hours using a magnetic stirrer, and then filtering the mixture using a syringe and a filter tip combination to prepare a lead iodide precursor solution;
[0156] 3-2) Preparation of ammonium salt precursor solution: using 1 ml of isopropanol as solvent, dissolving 60 mg of FAI, 6 mg of MACl, and 6 mg of MABr in a certain proportion, and then filtering with a syringe and a filter tip combination to prepare an ammonium salt precursor solution;
[0157] 3-3) Preparation of lead iodide layer: In a nitrogen glove box, 80-100 μL of lead iodide precursor solution is spin-coated onto the electron conduction layer at a speed of 1500 rpm and an acceleration of 800 m / s². After the spin coating, annealing is performed on a hot plate at 70°C for 1 minute to form a lead iodide layer;
[0158] 3-4) Preparation of perovskite light-absorbing layer: After blowing nitrogen on the surface, 100 μL of ammonium salt precursor solution is spin-coated on the lead iodide layer at a speed of 1500-1700 rpm, and then heated at 70°C in a nitrogen glove box for 50-60 seconds, and then heated to 150°C in an indoor air environment with a humidity of 45%-60%, and kept warm for 15 minutes to obtain a prolineamide-doped perovskite light-absorbing layer.
[0159] 4. Preparation of proline modified layer on perovskite light absorbing layer
[0160] 4-1) Preparation of Proline Modified Layer Solution
[0161] Prepare 1 mL of mixed solvent with ultrapure water: DMF: DMSO = 200 μL: 700 μL: 100 μL, add 1.2 mg of proline to make the proline concentration 1.2 mg / ml, heat to 70°C and stir until dissolved;
[0162] 4-2) In a nitrogen glove box, 40 μL of the proline modification layer solution was spin-coated onto the perovskite layer at a rotation speed of 4000 rpm for 30 seconds, and then heated and annealed at 75° C. for 1 minute to prepare a proline modification layer.
[0163] 5. Preparation of hole conduction layer on proline modified layer
[0164] 5-1) Preparation of hole conduction layer solution: dissolve Li-TFSI in acetonitrile to prepare a Li-TFSI acetonitrile solution with a concentration of 520 mg / ml; dissolve 0.0723 g of Spiro-MeOTAD in 1 ml of chlorobenzene as solvent, add 28.5 μL of tBP and 17.5 μL of Li-TFSI acetonitrile solution, stir for 1 hour, and filter with a syringe and filter tip combination to obtain a hole conduction layer solution;
[0165] 5-2) In a nitrogen glove box, 50 μL of the hole conduction layer solution was spin coated onto the proline modified layer at 4000 rpm for 30 seconds to prepare a hole conduction layer. After the spin coating, the layer was placed in a culture dish, and the culture dish was placed in a drying oven for oxidation under air conditions for 24 hours.
[0166] 6. Preparation of metal electrode layer
[0167] The metal electrode layer is prepared by sputtering a metal silver (Ag) electrode on the hole conduction layer using an evaporation deposition method.
[0168] Comparative Example 1:
[0169] 1. Conductive base treatment
[0170] 1-1) Preparing a substrate cleaning solution: mixing deionized water, glass cleaner, and dishwashing liquid in a volume ratio of 30:5:1 to obtain a substrate cleaning solution;
[0171] 1-2) ITO conductive glass is used, with a square resistance of 15, a transmittance of 93%, and a substrate size of 15*15mm 2 , 0.7 mm thick;
[0172] 1-3) After the conductive substrate is partitioned by laser engraving, the conductive substrate is scrubbed with a non-woven fabric soaked in a substrate cleaning solution, and then rinsed with deionized water and anhydrous ethanol in sequence. After the rinsing is completed, ultrasonic cleaning is performed with a substrate cleaning solution, ethanol, deionized water, acetone, and ethanol in sequence to obtain a clean conductive base layer;
[0173] 1-4) The cleaned conductive substrate is blown dry with nitrogen and subjected to UV-ozone treatment for 15 minutes.
[0174] 2. Prepare an electronic conduction layer on a conductive base layer
[0175] 2-1) Preparation of electron conduction layer solution: Use a pipette to take 500 μL of tin dioxide nanocrystal solution and 2 ml of deionized water, mix them evenly, and filter them through a syringe and filter tip combination to obtain an electron conduction layer solution;
[0176] 2-2) In an air environment and at room temperature, 70 μL of the electron conduction layer solution is taken with a pipette and spin-coated onto the conductive substrate at a spin-coating speed of 3000 rpm. After the spin-coating is completed, the solution is annealed on a 150° C. hot plate for 30 minutes, and then subjected to UV-ozone treatment to prepare an electron conduction layer.
[0177] 3. Preparation of prolineamide-doped perovskite light-absorbing layer on the electron conduction layer
[0178] 3-1) Preparing a lead iodide precursor solution: dissolving 600 mg of lead iodide in a mixed solvent of 900 μL of DMF and 100 μL of DMSO, heating and stirring at 70° C. for 12 hours using magnetic stirring, and then filtering using a syringe and filter tip combination to prepare a lead iodide precursor solution;
[0179] 3-2) Preparation of ammonium salt precursor solution: using 1 ml of isopropanol as solvent, dissolving 60 mg of FAI, 6 mg of MACl, and 6 mg of MABr in a certain proportion, and then filtering with a syringe and a filter tip combination to prepare an ammonium salt precursor solution;
[0180] 3-3) Preparation of lead iodide layer: In a nitrogen glove box, 80-100 μL of lead iodide precursor solution is spin-coated onto the electron conduction layer at a speed of 1500 rpm and an acceleration of 800 m / s². After the spin coating, annealing is performed on a hot plate at 70°C for 1 minute to form a lead iodide layer;
[0181] 3-4) Preparation of perovskite light-absorbing layer: After blowing nitrogen on the surface, 100 μL of ammonium salt precursor solution is spin-coated on the lead iodide layer at a speed of 1500-1700 rpm, and then heated at 70°C in a nitrogen glove box for 50-60 seconds, and then heated to 150°C in an indoor air environment with a humidity of 45%-60%, and kept warm for 15 minutes to obtain a prolineamide-doped perovskite light-absorbing layer.
[0182] 4. Preparation of hole conduction layer in perovskite light absorption layer
[0183] 4-1) Preparation of hole conduction layer solution: dissolve Li-TFSI in acetonitrile to prepare a Li-TFSI acetonitrile solution with a concentration of 520 mg / ml; dissolve 0.0723 g of Spiro-MeOTAD in 1 ml of chlorobenzene as solvent, add 28.5 μL of tBP and 17.5 μL of Li-TFSI acetonitrile solution, stir for 1 hour, and filter with a syringe and filter tip combination to obtain a hole conduction layer solution;
[0184] 5-2) In a nitrogen glove box, 50 μL of the hole conduction layer solution was spin coated onto the proline modified layer at 4000 rpm for 30 seconds to prepare a hole conduction layer. After the spin coating, the layer was placed in a culture dish, and the culture dish was placed in a drying oven for oxidation under air conditions for 24 hours.
[0185] 5. Preparation of metal electrode layer
[0186] The metal electrode layer is prepared by sputtering a metal silver (Ag) electrode on the hole conduction layer using an evaporation deposition method.
[0187] Comparative Example 2:
[0188] 1. Conductive base treatment
[0189] 1-1) Preparing a substrate cleaning solution: mixing deionized water, glass cleaner, and dishwashing liquid in a volume ratio of 30:5:1 to obtain a substrate cleaning solution;
[0190] 1-2) ITO conductive glass is used, with a square resistance of 15, a transmittance of 93%, and a substrate size of 15*15mm 2 , 0.7 mm thick;
[0191] 1-3) After the conductive substrate is partitioned by laser engraving, the conductive substrate is scrubbed with a non-woven fabric soaked in a substrate cleaning solution, and then rinsed with deionized water and anhydrous ethanol in sequence. After the rinsing is completed, ultrasonic cleaning is performed with a substrate cleaning solution, ethanol, deionized water, acetone, and ethanol in sequence to obtain a clean conductive base layer;
[0192] 1-4) The cleaned conductive substrate is blown dry with nitrogen and subjected to UV-ozone treatment for 15 minutes.
[0193] 2. Prepare an electronic conduction layer on a conductive base layer
[0194] 2-1) Preparation of electron conduction layer solution: Use a pipette to take 500 μL of tin dioxide nanocrystal solution and 2 ml of deionized water, mix them evenly, and filter them through a syringe and filter tip combination to obtain an electron conduction layer solution;
[0195] 2-2) In an air environment and at room temperature, 70 μL of the electron conduction layer solution is taken with a pipette and spin-coated onto the conductive substrate at a spin-coating speed of 3000 rpm. After the spin-coating is completed, the solution is annealed on a 150° C. hot plate for 30 minutes, and then subjected to UV-ozone treatment to prepare an electron conduction layer.
[0196] 3. Preparation of prolineamide-doped perovskite light-absorbing layer on the electron conduction layer
[0197] 3-1) Preparing a lead iodide precursor solution: dissolving 600 mg of lead iodide and 10 mg of proline amide in a mixed solvent of 900 μL of DMF and 100 μL of DMSO to obtain a proline amide concentration of 10 mg / ml, heating and stirring the mixture at 70° C. for 12 hours using a magnetic stirrer, and then filtering the mixture using a syringe and a filter tip combination to prepare a lead iodide precursor solution;
[0198] 3-2) Preparation of ammonium salt precursor solution: using 1 ml of isopropanol as solvent, dissolving 60 mg of FAI, 6 mg of MACl, and 6 mg of MABr in a certain proportion, and then filtering with a syringe and a filter tip combination to prepare an ammonium salt precursor solution;
[0199] 3-3) Preparation of lead iodide layer: In a nitrogen glove box, 80-100 μL of lead iodide precursor solution is spin-coated onto the electron conduction layer at a speed of 1500 rpm and an acceleration of 800 m / s². After the spin coating, annealing is performed on a hot plate at 70°C for 1 minute to form a lead iodide layer;
[0200] 3-4) Preparation of perovskite light-absorbing layer: After blowing nitrogen on the surface, 100 μL of ammonium salt precursor solution is spin-coated on the lead iodide layer at a speed of 1500-1700 rpm, and then heated at 70°C in a nitrogen glove box for 50-60 seconds, and then heated to 150°C in an indoor air environment with a humidity of 45%-60%, and kept warm for 15 minutes to obtain a prolineamide-doped perovskite light-absorbing layer.
[0201] 4. Preparation of proline modified layer on perovskite light absorbing layer
[0202] 4-1) Preparation of Proline Modified Layer Solution
[0203] Prepare 1 mL of mixed solvent with ultrapure water: DMF: DMSO = 200 μL: 700 μL: 100 μL, add 0.75 mg of proline to make the proline concentration 0.75 mg / ml, heat to 70°C and stir until dissolved;
[0204] 4-2) In a nitrogen glove box, 40 μL of the proline modification layer solution was spin-coated onto the perovskite layer at a rotation speed of 4000 rpm for 30 seconds, and then heated and annealed at 75° C. for 1 minute to prepare a proline modification layer.
[0205] 5. Preparation of hole conduction layer on proline modified layer
[0206] 5-1) Preparation of hole conduction layer solution: dissolve Li-TFSI in acetonitrile to prepare a Li-TFSI acetonitrile solution with a concentration of 520 mg / ml; dissolve 0.0723 g of Spiro-MeOTAD in 1 ml of chlorobenzene as solvent, add 28.5 μL of tBP and 17.5 μL of Li-TFSI acetonitrile solution, stir for 1 hour, and filter with a syringe and filter tip combination to obtain a hole conduction layer solution;
[0207] 5-2) In a nitrogen glove box, 50 μL of the hole conduction layer solution was spin coated onto the proline modified layer at 4000 rpm for 30 seconds to prepare a hole conduction layer. After the spin coating, the layer was placed in a culture dish, and the culture dish was placed in a drying oven for oxidation under air conditions for 24 hours.
[0208] 6. Preparation of metal electrode layer
[0209] The metal electrode layer is prepared by sputtering a metal silver (Ag) electrode on the hole conduction layer using an evaporation deposition method.
[0210] Comparative Example 3:
[0211] 1. Conductive base treatment
[0212] 1-1) Preparing a substrate cleaning solution: mixing deionized water, glass cleaner, and dishwashing liquid in a volume ratio of 30:5:1 to obtain a substrate cleaning solution;
[0213] 1-2) ITO conductive glass is used, with a square resistance of 15, a transmittance of 93%, and a substrate size of 15*15mm 2 , 0.7 mm thick;
[0214] 1-3) After the conductive substrate is partitioned by laser engraving, the conductive substrate is scrubbed with a non-woven fabric soaked in a substrate cleaning solution, and then rinsed with deionized water and anhydrous ethanol in sequence. After the rinsing is completed, ultrasonic cleaning is performed with a substrate cleaning solution, ethanol, deionized water, acetone, and ethanol in sequence to obtain a clean conductive base layer;
[0215] 1-4) The cleaned conductive substrate is blown dry with nitrogen and subjected to UV-ozone treatment for 15 minutes.
[0216] 2. Prepare an electronic conduction layer on a conductive base layer
[0217] 2-1) Preparation of electron conduction layer solution: Use a pipette to take 500 μL of tin dioxide nanocrystal solution and 2 ml of deionized water, mix them evenly, and filter them through a syringe and filter tip combination to obtain an electron conduction layer solution;
[0218] 2-2) In an air environment and at room temperature, 70 μL of the electron conduction layer solution is taken with a pipette and spin-coated onto the conductive substrate at a spin-coating speed of 3000 rpm. After the spin-coating is completed, the solution is annealed on a 150° C. hot plate for 30 minutes, and then subjected to UV-ozone treatment to prepare an electron conduction layer.
[0219] 3. Preparation of prolineamide-doped perovskite light-absorbing layer on the electron conduction layer
[0220] 3-1) Preparing a lead iodide precursor solution: dissolving 600 mg of lead iodide and 1 mg of proline amide in a mixed solvent of 900 μL of DMF and 100 μL of DMSO to obtain a proline amide concentration of 1 mg / ml, heating and stirring the mixture at 70° C. for 12 hours using a magnetic stirrer, and then filtering the mixture using a syringe and a filter tip combination to prepare a lead iodide precursor solution;
[0221] 3-2) Preparation of ammonium salt precursor solution: using 1 ml of isopropanol as solvent, dissolving 60 mg of FAI, 6 mg of MACl, and 6 mg of MABr in a certain proportion, and then filtering with a syringe and a filter tip combination to prepare an ammonium salt precursor solution;
[0222] 3-3) Preparation of lead iodide layer: In a nitrogen glove box, 80-100 μL of lead iodide precursor solution is spin-coated onto the electron conduction layer at a speed of 1500 rpm and an acceleration of 800 m / s². After the spin coating, annealing is performed on a hot plate at 70°C for 1 minute to form a lead iodide layer;
[0223] 3-4) Preparation of perovskite light-absorbing layer: After blowing nitrogen on the surface, 100 μL of ammonium salt precursor solution is spin-coated on the lead iodide layer at a speed of 1500-1700 rpm, and then heated at 70°C in a nitrogen glove box for 50-60 seconds, and then heated to 150°C in an indoor air environment with a humidity of 45%-60%, and kept warm for 15 minutes to obtain a prolineamide-doped perovskite light-absorbing layer.
[0224] 4. Preparation of hole conduction layer in perovskite light absorption layer
[0225] 4-1) Preparation of hole conduction layer solution: dissolve Li-TFSI in acetonitrile to prepare a Li-TFSI acetonitrile solution with a concentration of 520 mg / ml; dissolve 0.0723 g of Spiro-MeOTAD in 1 ml of chlorobenzene as solvent, add 28.5 μL of tBP and 17.5 μL of Li-TFSI acetonitrile solution, stir for 1 hour, and filter with a syringe and filter tip combination to obtain a hole conduction layer solution;
[0226] 4-2) In a nitrogen glove box, 50 μL of the hole conduction layer solution was spin coated onto the proline modified layer at 4000 rpm for 30 seconds to prepare a hole conduction layer. After the spin coating, the layer was placed in a culture dish, and the culture dish was placed in a drying oven for oxidation under air conditions for 24 hours.
[0227] 5. Preparation of metal electrode layer
[0228] The metal electrode layer is prepared by sputtering a metal silver (Ag) electrode on the hole conduction layer using an evaporation deposition method.
[0229] Effect example:
[0230] The perovskite solar cells of Examples 1 to 5 and Comparative Examples 1 to 3 were subjected to JV curve tests. Figure 2 and Figure 3 shown.
[0231] The perovskite solar cells obtained in Example 1 and Comparative Example 1 were subjected to quantum efficiency (EQE) test, electrochemical impedance spectroscopy (EIS) test, dark current density-voltage (Dark JV) curve test, space charge limited current method (SCLC) test, X-ray diffraction (XRD) test, UV-visible absorption spectrum and Tacu-plot, UV photoelectron spectrum and photoelectric conversion efficiency stability test. Figure 4-Figure 14 The test results are as follows:
[0232] The perovskite solar cell prepared in Example 1 had an average photoelectric conversion efficiency of 22.52% under a simulated sunlight environment, and a maximum photoelectric conversion efficiency of 22.97%.
[0233] The perovskite solar cell prepared in Example 2 had an average photoelectric conversion efficiency of 20.89% under a simulated sunlight environment, and a maximum photoelectric conversion efficiency of 21.13%.
[0234] The perovskite solar cell prepared in Example 3 had an average photoelectric conversion efficiency of 21.56% under a simulated sunlight environment, and a maximum photoelectric conversion efficiency of 21.70%.
[0235] The perovskite solar cell prepared in Example 4 had an average photoelectric conversion efficiency of 21.32% under a simulated sunlight environment, and the highest photoelectric conversion efficiency was 21.79%.
[0236] The perovskite solar cell prepared in Example 5 had an average photoelectric conversion efficiency of 21.24% under a simulated sunlight environment, and a maximum photoelectric conversion efficiency of 21.65%.
[0237] The perovskite solar cell prepared in Comparative Example 1 had an average photoelectric conversion efficiency of 18.97% under a simulated sunlight environment, and a maximum photoelectric conversion efficiency of 19.25%.
[0238] The perovskite solar cell prepared in Comparative Example 2 has an average photoelectric conversion efficiency of 19.79% under simulated sunlight, and a maximum photoelectric conversion efficiency of 20.44%. The reason may be that due to the excessive doping amount, the additives destroyed the lattice structure of the perovskite, thereby affecting the normal transport of carriers, resulting in the additives having an adverse effect on the photoelectric performance of the device.
[0239] The perovskite solar cell prepared in Comparative Example 3 had an average photoelectric conversion efficiency of 20.60% under a simulated sunlight environment, and a maximum photoelectric conversion efficiency of 20.82%.
[0240] In addition, the performance comparison between Example 1 and Comparative Example 1 is as follows:
[0241] Depend on Figure 4 It can be seen that the perovskite solar cell prepared in Example 1 has a higher quantum efficiency than that of Comparative Example 1 in which prolineamide is not added and proline is not modified. Figure 4 The integrated current density-wavelength curve obtained by quantum efficiency is also included, and it can be found that the integrated current density of Example 1 (23.26 mA / cm 2 ) is higher than that of comparative example 1 (22.78 mA / cm 2 ), and is consistent with the current density-voltage test results.
[0242] Depend on Figure 5 It can be seen that after being treated with prolineamide and proline (Example 1), the interface transfer resistance of the device is reduced from 17.4 kΩ to 8.7 kΩ, indicating that the interface obstacles received by the carriers in the normal transport process are smaller, and the interface defects between the electron conduction layer and the perovskite layer and between the hole conduction layer and the perovskite layer are passivated.
[0243] Depend on Figure 6 It can be seen that after the treatment with prolineamide and proline (Example 1), the dark state leakage current is significantly reduced, indicating that the loss of effective current is reduced.
[0244] Depend on Figure 7 and Figure 8 It can be seen that the voltage corresponding to the intersection of the two fitting lines (V TFL ) It is inferred that the defect state density of the perovskite layer material in comparative example 1 is: 1.29×10 16 / cm 2 , while the defect state density of the perovskite layer material in Example 1 is reduced to: 9.98×10 15 / cm 2 .
[0245] Fig. 9 The diffraction peak at 12.8° belongs to PbI2, and the diffraction peak at about 14.2° belongs to the characteristic peak of the (110) crystal plane of perovskite. It shows that after the doping of prolineamide and the modification of proline, there is less unreacted residual perovskite precursor PbI2, and the characteristic diffraction peak of the perovskite layer material is higher, and its crystallinity is stronger.
[0246] Depend on Fig.10 It can be seen that the light absorption capacity of the perovskite layer is enhanced after prolineamide treatment (Example 1). The bandgap widths of the perovskite layer material before (Example 1) and after (Comparative Example 1) prolineamide treatment are 1.583 eV and 1.579 eV respectively after calculation and fitting using the Tacu-plot method. Fig.11 Curve fitting shows that the valence band top energy level of the perovskite layer before and after prolineamide treatment is -5.89 eV and -5.79 eV. Combined with its band gap width, the conduction band bottom energy level of the perovskite layer before and after prolineamide treatment is -4.277 eV and -4.21 eV. After prolineamide treatment, the energy level of the perovskite layer material moves up, which is more conducive to the transmission of electrons to the electron conduction layer through the energy level matching effect.
[0247] Depend on Figure 12-14 It is shown that the photoelectric conversion efficiency of the perovskite solar cell obtained in Example 1 is 21.21% after being stored in a nitrogen glove box environment for 720 hours in the dark, 18.24% after being continuously irradiated with a standard solar intensity for 240 hours, and 16.85% after being stored in an air environment with a humidity of 40%-60% for 720 hours; while the photoelectric conversion efficiency of the perovskite solar cell obtained in Comparative Example 1 is 15.82% after being stored in a nitrogen glove box environment for 720 hours in the dark, 7.84% after being continuously irradiated with a standard solar intensity for 240 hours, and 10.81% after being stored in an air environment with a humidity of 40%-60% for 720 hours. Its stability is poor.
[0248] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a perovskite solar cell after crystallization control, characterized in that: The method comprises: (1) Blowing the cleaned conductive substrate dry with nitrogen and performing UV-ozone treatment; (2) preparing an electronic conduction layer on the conductive base layer; (3) preparing a prolineamide calcium-doped perovskite light-absorbing layer on the electron conduction layer; (4) Preparing a proline modified layer on the perovskite light absorbing layer; (5) preparing a hole conduction layer on the proline modified layer; (6) Sputtering a metal electrode on the hole conduction layer using a magnetron sputtering apparatus or an evaporation deposition method to prepare a metal electrode layer.
2. The method for preparing a perovskite solar cell after crystallization control according to claim 1, characterized in that: Step (1) includes: After the conductive base layer is partitioned by laser engraving, the conductive base layer is scrubbed with a non-woven fabric soaked in a base cleaning solution, and then rinsed with deionized water and anhydrous ethanol in sequence. After the rinsing is completed, ultrasonic cleaning is performed with a base cleaning solution, ethanol, deionized water, acetone, and ethanol in sequence for 15 minutes to obtain a clean conductive base layer; The substrate cleaning solution is obtained by uniformly mixing deionized water, glass cleaner and dishwashing liquid in a volume ratio of 30:5:
1.
3. The method for preparing a perovskite solar cell after crystallization control according to claim 1, characterized in that: The step (2) comprises: In an air environment and at room temperature, 70 μL of the electron conduction layer solution is taken with a pipette and spin-coated onto the conductive base layer at a spin-coating speed of 3000 rpm. After the spin-coating is completed, the solution is annealed on a 150° C. hot stage for 30 minutes, and then subjected to UV-ozone treatment to prepare an electron conduction layer. The electronic conduction layer solution is obtained by uniformly mixing a tin dioxide nanocrystal solution and deionized water in a volume ratio of 1:4, and filtering the mixture through a syringe and a filter nozzle combination.
4. The method for preparing a perovskite solar cell after crystallization control according to claim 1, characterized in that: The step (3) comprises: In a nitrogen glove box, 80-100 μL of a lead iodide precursor solution is spin-coated onto the electron conduction layer at a speed of 1500 rpm and an acceleration of 800 m / s². After the spin coating, the lead iodide layer is annealed on a hot plate at 70°C for 1 minute to form a lead iodide layer. After nitrogen is blown on the surface, 100-110 μL of ammonium salt precursor solution is spin-coated on the lead iodide layer at a speed of 1500-1700 rpm; heated at 70° C. for 50-60 seconds in a nitrogen glove box, and then heated to 150° C. in an indoor air environment with a humidity of 45%-60%, and kept warm for 15 minutes to obtain a prolineamide-doped perovskite light-absorbing layer.
5. The method for preparing a perovskite solar cell after crystallization control according to claim 4, characterized in that: The lead iodide precursor solution is prepared by mixing lead iodide and prolineamide in a certain proportion, adding the mixture to a solvent of N,N-dimethylformamide and dimethyl sulfoxide mixed in a volume ratio of 9:1 to dissolve the mixture so that the prolineamide concentration is 0.5-1.5 mg / mL, continuously heating and stirring the mixture at 60-70° C., and filtering the mixture through a syringe and a filter tip combination.
6. The method for preparing a perovskite solar cell after crystallization control according to claim 4, characterized in that: The ammonium salt precursor solution is obtained by adding iodoformamidine, chloromethylamine and bromomethylamine in a mass ratio of (9-10):(2-1):1 to an isopropanol solution and dissolving the solution, and then filtering the solution through a syringe and a filter nozzle combination.
7. The method for preparing a perovskite solar cell after crystallization control according to claim 1, characterized in that: Step (4) includes: Proline is added to a mixed solvent of ultrapure water, N,N-dimethylformamide, and dimethyl sulfoxide in a volume ratio of 2:7:1, so that the concentration of proline is 0.3-1.2 mg / mL; In a nitrogen glove box, 40 μL of the proline modification layer solution was spin-coated onto the perovskite light-absorbing layer at a rotation speed of 4000 rpm for 30 seconds, and then heated and annealed at 75° C. for 1 minute to prepare a proline modification layer.
8. The method for preparing a perovskite solar cell after crystallization control according to claim 1, characterized in that: Step (5) comprises: spin coating 50 μL of the hole conduction layer solution onto the proline modified layer at a speed of 4000 rpm for 30 seconds in a nitrogen glove box to prepare a hole conduction layer, and placing the layer in a drying oven for oxidation for 24 hours after the spin coating is completed.
9. The method for preparing a perovskite solar cell after crystallization control according to claim 1, characterized in that: The hole conduction layer solution is prepared as follows: Using acetonitrile as solvent to dissolve Li-TFSI to prepare a Li-TFSI acetonitrile solution with a concentration of 520 mg / mL; Spiro-OMeTAD is dissolved in chlorobenzene as a solvent, tBP and the Li-TFSI acetonitrile solution are added, and then filtered through a syringe and filter tip combination to obtain the product.
10. A perovskite solar cell according to any one of claims 1 to 9.
Citation Information
Patent Citations
Dopamine-doped perovskite solar cell and preparation method thereof
CN111540830A
Perovskite solar cell and preparation method thereof
CN114497390A